COGNITIVE PROCESSES AND CONCEPTUAL FOUNDATIONS IN BIOTECHNOLOGICAL TERMINOLOGY (International journal of artificial intelligence, 2026)
This article examines cognitive processes and conceptual foundations underlying biotechnological terminology. The study focuses on cognitive modeling of terms, conceptual metaphors, and categorization mechanisms involved in the formation of biotechnological concepts. Special attention is paid to the semantic and structural characteristics of biotechnological terms within scientific discourse. The findings contribute to the fields of terminology studies, cognitive linguistics, and interdisciplinary research by providing both theoretical insights and practical implications.